Dificultad de atención a la lectura y su incidencia en el proceso de enseñanza aprendizaje - Benítez Ortiz, Lid Corin (2018)
The teaching - learning process in educational institutions entails, among others, a social process of construction of knowledge by teachers and students. They interact by teaching and learning from the different subjects proposed by the curriculum for the different levels of education. In this sense, a good teaching-learning process in any domain of knowledge, energized by teachers, must be promoted by the motivation or need to carry out the entrusted activities. Under this consideration it is necessary to determine the influence of attention to reading in the development of the teaching-learning process, for which the case study is carried out, where it is applied to a student with a greater presence of attention deficit for reading. of some that exist in the Maria Andrea Educational Unit of the city of Babahoyo, Province of Los Ríos, with the exploratory method that offers a first approach to the problem that is intended to be investigated and known. It is done to know the topic that will be addressed, which allows us to "familiarize" ourselves with something that until now was unknown. Applying techniques such as the interview, formally with semi-structured questions for the teacher, which aims to obtain information regarding behavior, affinity for reading and academic performance of the student, concluding that students in the study have difficulty attending to the reading, they are motivated very little by the readings that the same one selected previously, besides it presents / displays hyperactivity during the development of its scholastic activities.